Bioapplication of graphene oxide derivatives: Drug/gene delivery, imaging, polymeric modification, toxicology, therapeutics and challenges - Nurunnabi, Md; Parvez, Khaled; Nafiujjaman, Md; Revuri, Vishnu; Khan, Haseeb A.; Feng, Xinliang; Lee, Yong-Kyu (RSC Advances, 2015)
Due to the wide range and various applications of graphene in multidisciplinary fields, such as electronics, solar cells, biomedicine, bioengineering, drug delivery, gene delivery and semiconductors, graphene and its derivatives have attracted most significant interest of diverse group of scientists in the last decades. Besides numerous applications in electrical and mechanical fields, their non-invasive biomedical imaging properties allow their wide-spread biological applications. Optical imaging probes play a pivotal role in early cancer detection, image based surgery, disease diagnosis and cellular imaging. Graphene has been widely studied in drug delivery systems due to its unique features and comparatively less/non-toxic properties in biological systems, thus promoting graphene quantum dots as potential organic optical imaging agents to substitute toxic cadmium or tellurium quantum dots. Many groups have also focused on different polymeric modification strategies to enhance the biocompatibility as well as the applications of graphene. In this review, we have summarized recent advances in graphene-based applications, and focused on the relation between chemical structure and polymeric modification with bio-safety issues. The lack of adequate biosafety studies and understanding of the interaction between graphene derivatives and biomolecules has hindered their progress in biomedical and biological applications. To proceed with biological applications of graphene derivatives, such as the development of graphene-based therapeutics and drug delivery systems, the research community must understand how graphene derivatives interact with cell lines and how they accumulate into cells. We also need to learn the fate of graphene derivatives in vivo once it invasively enters into a biological system.
CRIS-Team Scopus Importer:2023-03-20